Managing School Culture on Excellent Elementary School in East Java Indonesia - Muhammad Walid; Lutfiya Qomaril Uyun (Al Ibtida: Jurnal Pendidikan Guru MI, 2020)
AbstractThis research aims to find out how a school culture in an Excellent School in East Java is managed so that it can shape students' characters. This study is descriptive-qualitative approach. The data collection performed through observation, interview, and documentation. The data analysis is conducted by reducing irrelevant data, presenting data and drawing a conclusion. In anlyzing the data validity, researcher used a credibility test by using data triangulation and member check. The research findings indicate that the excellent school culture management process in East Java has several steps such as planning, organizing, implementation, and evaluation. The strategies in developing the school culture are schoolâ€™s routine activity/habituating, spontaneous activity/habituating, modeling and conditioning. The strategies are applied through modeling, teaching, and reinforcing. It implies that the principal of school play a strong role in student character education.Keywords: management, school culture, excellent school.Â AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana sebuah budaya sekolah pada sekolah unggulan di Jawa Timur dikelola sehingga dapat membentuk karakter siswa. Penelitian ini adalah penelitian kualitatif deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, sedang analisis data dilakukan dengan mereduksi, memaparkan dan menyimpulkan. Untuk keabsahan data diuji dengan uji kredibilitas; triangulasi data, dan member check. Hasil penelitian menunjukkan bahwa proses pengelolaan budaya sekolah unggulan di Jawa Timur memiliki beberapa tahapan, yaitu perencanaan, pengorganisasian, pelaksanaan, dan pengevaluasian. Strategi pengembangan budaya sekolah pada sekolah unggulan diantaranya dilakukan dengan kegiatan rutin di sekolah, aktivitas spontan, keteladanan, dan pengkondisian. Adapun strategi pelaksanaannya menggunakan pemodelan (modeling), pengajaran (teaching), dan penguatan lingkungan (reinforcing). Implikasi dari temuan ini adalah bahwa pengelola sekolah memainkan peranan yang sangat penting dalam pembentukan karakter siswa.Kata kunci: pengelolaan, budaya sekolah, sekolah unggulan.Â